Creating a patient registry as a framework for developing a hepatitis C program at a Federally Qualified Health Center. Issue 1 (2nd January 2022) - Zepeda Orozco, Michelle; Magner, Bridget
Abstract: Hepatitis C has become a silent epidemic in the United States. Many are unaware of their status and are left untreated, especially among at risk populations due to barriers prohibiting access to care. Therefore, it is important to establish Hepatitis C treatment programs in health centers that serve these communities. This project involved creating the groundwork for the development of a Hepatitis C program at a federally qualified health center primarily serving a low-income, minority population. Program development included creating a patient registry, identifying best practices, and participating in HCV case management and capacity building trainings. When accompanied with evidence-based practices, the inclusion of the registry will enhance Hepatitis C programs to be able to address the needs and effectively respond to the HCV crisis.